New Development of Flow Field Calibration in the 2.4 m Transonic Wind Tunnel. (August 2019) - Chen, Xuekong; Lin, Xuedong; Zhang, Lin; Liu, Guangyuan; Wang, Ruibo
Abstract: For the purpose of improving the flow fields of CARDC's 2.4 m transonic wind tunnel in accuracy, two types of calibrations have been done in this tunnel. One was designing and manufacturing a new centerline pipe in high quality to calibrate the centreline flow, obtaining the accurate Mach number correction relationships and helped to build up new flow fields in accuracy. The other was applying a cone-cylinder model to measure the symmetries of the longitudinal flow fields to simulate the testing articles' movement in pitching zone. It helped to investigate the detailed information of this flow fields. Based on these, the flow fields in higher accuracy were built up in the full-span model test section. This article presents the method, the process and the results of the calibrations herein.